2005
DOI: 10.1521/suli.2005.35.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Social Risk and Protective Factors for Suicide Attempts in Low Income African American Men and Women

Abstract: A case-control study was conducted to examine a broad array of potential social risk and protective factors for suicide attempt among 200 African American men and women receiving care at a large, public, urban hospital. Specifically, we examined the effect of the following potential risk factors for suicide attempt: life hassles, partner abuse, partner dissatisfaction, and racist events; as well as the following potential protective factors: effectiveness of obtaining resources, social embeddedness, and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 59 publications
4
48
0
Order By: Relevance
“…Additionally, social support is protective against a range of mental health problems and has been linked to lowered odds of being diagnosed with depression (Chatters et al, 2015; Lincoln & Chae, 2012; Lincoln, Taylor, Chae, & Chatters, 2010; Taylor et al, 2015), anxiety (Levine, Taylor, Nguyen, Chatters, & Himle, in press; Lincoln, Taylor, Bullard, et al, 2010), fewer depressive symptoms (Haines, Beggs, & Hurlbert, 2008; Lincoln, Chatters, & Taylor, 2005), and lower levels of psychological distress (Lincoln, Chatters, & Taylor, 2003). Conversely, African Americans experiencing low levels of social support are more likely to have suicidal ideation (Lincoln, Taylor, Chatters, & Joe, 2012; Wingate et al, 2005) and to attempt suicide (Compton, Thompson, & Kaslow, 2005; Kaslow et al, 2005; Lincoln, Taylor, Chatters, et al, 2012). More specifically, smaller social support network size and decreased frequency of contact with one’s support network are correlated with higher rates of suicide completion (Turvey et al, 2002).…”
Section: Informal Support Negative Interactions and Mental Health Amentioning
confidence: 99%
“…Additionally, social support is protective against a range of mental health problems and has been linked to lowered odds of being diagnosed with depression (Chatters et al, 2015; Lincoln & Chae, 2012; Lincoln, Taylor, Chae, & Chatters, 2010; Taylor et al, 2015), anxiety (Levine, Taylor, Nguyen, Chatters, & Himle, in press; Lincoln, Taylor, Bullard, et al, 2010), fewer depressive symptoms (Haines, Beggs, & Hurlbert, 2008; Lincoln, Chatters, & Taylor, 2005), and lower levels of psychological distress (Lincoln, Chatters, & Taylor, 2003). Conversely, African Americans experiencing low levels of social support are more likely to have suicidal ideation (Lincoln, Taylor, Chatters, & Joe, 2012; Wingate et al, 2005) and to attempt suicide (Compton, Thompson, & Kaslow, 2005; Kaslow et al, 2005; Lincoln, Taylor, Chatters, et al, 2012). More specifically, smaller social support network size and decreased frequency of contact with one’s support network are correlated with higher rates of suicide completion (Turvey et al, 2002).…”
Section: Informal Support Negative Interactions and Mental Health Amentioning
confidence: 99%
“…The second study involved African American men and women aged 18-64 years (n=200). Cases included 50 men and 50 women who were seen by medical or psychiatric services within 24 hours after a suicide attempt, and controls included 50 men and 50 women with no history of suicidal behavior who were seeking medical care in an urgent care clinic within the same hospital (Compton et al, 2004;Kaslow et al, 2004;Kaslow et al, 2005). Exclusionary criteria for both studies are detailed extensively in prior publications Thompson et al, 2002;Compton et al, 2004;Kaslow et al, 2004;Kaslow et al, 2005).…”
Section: Participantsmentioning
confidence: 99%
“…Meanwhile, psychiatry patients without suicidal ideation showed significantly lower mean scores on protective factors as compared to medical patients without suicidal ideation. These results were expected since psychiatry patients with suicidal ideation are known to have lower level to reasons for living, self esteem, hopefulness, social support and satisfaction with life Malone et al, 2000;Meadow et al, 2005;Kaslow et al, 2005;Nisbet and Lewinsohn et al, 1994.…”
Section: Protective Factors For Suicidal Ideationmentioning
confidence: 94%
“…Meanwhile, Kaslow et al, (2005) concluded in their study that suicide attempter's (African-American adult) status could be predicted by social support received among these group as compared to non-suicide attempters. Nisbet (1996) reported in his study that one of the protective factors for low suicide rates of black females in USA include social support from friends and family.…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation